Self-Acceptance of Broken Home Adolescents: Study on Sleman Regency - Saharaj, Saharaj; Yudhawati, Dian (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Being self-aware does not mean being self-critical; rather, it means having a high regard for yourself or your rival. Three factors are associated with self-acceptance: psychological well-being, acceptance of others, and our reluctance to communicate our thoughts, feelings, and reactions to others openly. Adults with broken homes background find that self-acceptance is crucial for their ability to adjust and develop tolerance for external conflict. This study uses self-acceptance theory to analyze. This study aims to discover how children’s dynamics of self-acceptance break down at the adolescent stage of life. Besides, it is expected that this study will help to provide new insights for parents who choose to separate from their children in the aftermath of a divorce. The study’s participants were 16–18-year-olds from broken homes in Sleman, Yogyakarta. This study combines a case study method with qualitative study techniques. Techniques for gathering data include documentation, observations, and interviews. The study’s findings showed Adolescents with broken home backgrounds do not mean that they cannot accept who they are. The pattern of parenting, the healthy bond between parents and children, the social support offered by the family and other social environments, and effective communication between the child and the parent are some of the factors that reinforce self-acceptance.